KONSEP PENDIDIKAN MULTIKULTURAL DALAM PENDIDIKAN ISLAM - Santi, Febri (Turast: Jurnal Penelitian dan Pengabdian, 2016)
Education is actually a study that is able to recognize, is able to accommodate all possibilities, understandheterogeneity, appreciate differences both tribes, nations, especially religion. These aspects are interconnectedwhich orients humanity. This course also aligned with one of the humanitarian orientation of multiculturaleducation in the context of the Qur’an is to seek recognition and understanding of SARA to understandheterogeneity, applying the multicultural nature of education itself. This study uses a qualitative approachphenomenologi.